A linkage study of progressive familial heart block using PCR-based detection of polymorphic loci and an investigation into the role of autoantibodies in this disease - Moolman, J. C.(Johanna Catharina) (Stellenbosch : Stellenbosch University, 2012)
One copy microfiche.